ARCHITECTURE AS IDENTIFICATION OF PLACE : THE CASE OF JOGLO KAMPUNG KETANDAN SURABAYA - Andy Mappajaya; Nur Endah Nuffida; Murni Rachmawati (Journal of Architecture&ENVIRONMENT, 2019)
To make a site become a place  is the existential function of architecture. The definition of architecture as identification of place (Unwin, 2003), comes with a purpose that architecture is also process to discover the essence, the meaning conceivably present in the given environment. In the case of Kampung Ketandan Surabaya, the architecture is produced by community by preserving and revitalizing the character of kampung, with regards of its history, its activities and its buildings. Balai Pertemuan Warga in the form of Pendhopo, is one from many other community centers in the kampung. This paper investigates in what way architecture generates symbolic places. Descriptive criticism is used as method to investigate the phenomenon by considering architecture as a way of art and find the interrelationship between the elements in it. To grasp the context of Kampung Ketandan, case study method is chosen because of its ability to explore and endowed the holistic, yet meaningful aspects of a presence phenomenon happened in real-life. The results of the study revealed that that place is holistic phenomenon, determine as an ‘environmental character’ and architecture is a symbol to identify it.